Spatial agency and practising architecture beyond buildings. (17th February 2017) - Lorne, Colin
Abstract: This paper provides new direction for geographic scholarship on architecture by focusing upon architectural projects that go well beyond designing and producing material objects. Recent work on practising architectures by social and cultural geographers has examined the multiple processes of human and non-human actors that cohere and congeal to produce buildings. Responding to concerns that geographers are failing to work closely with architects, I introduce ideas of spatial agency to examine the practices of architects working beyond buildings. Arguing that the profession has always been under threat, I outline why socially progressive architects are rejecting claims as expert technical problem-solvers or artistic form-givers by instead initiating and contributing towards explicitly spatial projects prioritizing social and economic objectives. By calling for creative engagement with such projects, I set forth an agenda for a politically progressive geography of architecture.